NGOs, health, and the urban poor - Nadkarni, Vimla V.; Sinha, Roopashri; D'Mello, Leonie (Jaipur : Rawat Publications, 2009)
Contributed articles with reference to India.
Includes bibliographical references and index.
Keywords: Urban poor -- Medical care -- India -- Bombay; Public health -- India -- Bombay; Women's health services -- India -- Bombay; Non-governmental organizations -- India -- Bombay